Pengujian aktivitas antimikroba ekstrak daun kersen (Mutingia calabura L.) menggunakan pelarut nades (Natural Deep Eutectic Solvents) dengan metode disc diffusion - Marliza, Hesti; Utami, Rury Trisa; Amelia, Ayu; Pratiwi, Reri (Arfak Chem: Chemistry Education Journal, 2025)
Antibiotic resistance is one of the significant global health challenges, prompting the search for new antimicrobial compounds from natural sources. One promising plant is cherry leaves (Muntingia calabura L.), which are known to contain flavonoids and other bioactive compounds with antibacterial potential. This study evaluated the antimicrobial activity of cherry leaf extract obtained through Ultrasound-Assisted Extraction (UAE) using Natural Deep Eutectic Solvents (NADES) as extraction solvents. Two types of NADES were used: a mixture of choline chloride: citric acid (1:2) and choline chloride: glycerol (1:2), which offer advantages such as low toxicity, high stability, non-volatility, and environmental friendliness compared to conventional organic solvents. Antimicrobial activity was assessed using the disc diffusion method against Escherichia coli and Staphylococcus aureus. The results showed that the extract using choline chloride: citric acid as solvent produced inhibition zones of 22.5 mm against E. coli and 16.05 mm against S. aureus. In contrast, the extract using choline chloride glycerol exhibited low activity against E. coli (3.41 mm) and was inactive against S. aureus. These findings indicate that combining UAE and citric acid-based NADES is an effective and sustainable approach for extracting bioactive compounds to develop natural antibacterial agents.